Applying smart antenna on soft handover by simulation using OPNET / Noor Muhammad Abd. Rahman - Abd. Rahman, Noor Muhammad (2006)
Mobile networks allow users to access services while on the move so giving end users "freedom" in terms of mobility. However, this freedom does bring uncertainties to mobile systems. The mobility of the end users causes dynamic variations both in the link quality and the interference level, sometimes requiring that a particular user change its serving base station. This process is known as handover (HO). Compared with the conventional hard handover employed in the Global System of Mobile (GSM) networks, the soft handover used in IS-95 and being proposed for third generation (3G) has better performance on both link and system level. In this project, the performances of soft handover are studied by applying smart antenna in OPNET Soft Handover model. Then, the simulation results are compared with soft handover that uses omni-directional antenna in terms of their performance in soft handover network.